MODEL PEMBELAJARAN BERMAKNA BERBASIS NILAI AL WASHLIYAH DALAM PENINGKATAN MUTU PENDIDIKAN BINAAN AL WASHLIYAH - Saiful Bahri, Samsul Bahri, (FKIP UMN ALWASHLIYAH, 2025)
This study aims to develop and test the effectiveness of the Al Washliyah Values-Based Meaningful Learning Model as a pedagogical approach capable of strengthening the quality of education in Al Washliyah's partner schools. The background to this research stems from Al Washliyah's internal need to provide a learning model that not only develops academic competencies but also instills Islamic values, Islamic values, and character in students holistically. Specifically, this study formulates a learning model that integrates Al Washliyah's core values ​​of faith, knowledge, and charity into meaningful learning stages, encompassing the activation of prior knowledge, the construction of new concepts,The research results show that the developed model has a very high level of validity from educational experts and Al Washliyah figures. Implementation of the model has also been proven to improve the quality of the learning process, student motivation, Islamic attitudes and character competencies, and teacher performance in planning and implementing values-based learning.internalization of values, and collaborative reflection within the context of teaching and learning activities.The research method used a research and development (R&D) approach using a modified Borg & Gall model in four stages: needs exploration, model design, expert validation, and limited implementation testing in three Al Washliyah partner schools. Data were collected through observation, interviews, questionnaires, and documentation analysis. Data were then processed qualitatively and quantitatively to assess the model's feasibility and its impact on improving learning quality. The findings of this study confirm that the integration of Al Washliyah values ​​into meaningful learning significantly enhances educational quality, particularly in Al Washliyah-supported institutions focused on developing knowledgeable, moral, and progressive individuals. This model is recommended as a pedagogical reference for Al Washliyah schools more broadly and can be developed for other Islamic educational institutions.